2015
DOI: 10.3389/fpls.2015.00052
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive control of plant growth: bearing the load, sensing, transducing, and responding

Abstract: As land plants grow and develop, they encounter complex mechanical challenges, especially from winds and turgor pressure. Mechanosensitive control over growth and morphogenesis is an adaptive trait, reducing the risks of breakage or explosion. This control has been mostly studied through experiments with artificial mechanical loads, often focusing on cellular or molecular mechanotransduction pathway. However, some important aspects of mechanosensing are often neglected. (i) What are the mechanical characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 82 publications
(186 reference statements)
2
84
0
1
Order By: Relevance
“…The physiological role of EBC in plant adaptive responses to salinity has been a matter of numerous experimental and review papers (see the Introduction section), but the reported evidence is mostly circumstantial. Here we show that the gentle removal of EBC, which did not cause any thigmomorphogenic response (Kamano et al 2015;Moulia et al 2015), results in a salt-sensitive phenotype. This provides the first direct evidence for a role of EBC in salt tolerance in halophytes.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The physiological role of EBC in plant adaptive responses to salinity has been a matter of numerous experimental and review papers (see the Introduction section), but the reported evidence is mostly circumstantial. Here we show that the gentle removal of EBC, which did not cause any thigmomorphogenic response (Kamano et al 2015;Moulia et al 2015), results in a salt-sensitive phenotype. This provides the first direct evidence for a role of EBC in salt tolerance in halophytes.…”
Section: Discussionmentioning
confidence: 72%
“…; Moulia et al . ), results in a salt‐sensitive phenotype. This provides the first direct evidence for a role of EBC in salt tolerance in halophytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the strains (= the sensed stimuli) were not quantified and the time resolution was too low to give insights into the processes by which thigmomorphogenesis takes place. From data on isolated cells, Moulia et al (2011Moulia et al ( , 2015 have suggested the existence of sensing thresholds but they did not measure them in whole-plant experiments. We may speculate that these thresholds could be tuned to the prevailing chronic loads.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical stimulus received by cells in the rosette leaves of plants that have been touched, sprayed, blown or bent must be transmitted to the cells of the shoot apical meristem in order to control elongation of the future shoot or stem (Moulia et al , 2015). …”
Section: Introductionmentioning
confidence: 99%